2013
DOI: 10.1590/s2317-17822013005000004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an educational program on the feeding of neurologically impaired children

Abstract: The educational program had a positive impact on the knowledge and conduct of caregivers concerning the feeding of their children with chronic non-progressive encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Thus, it is possible to infer that the mother is the main actor in child care, receiving help from her mother and her husband. Despite of this help, almost all participants did not any other labor outside the home, as in the study by Carvalho et al 17 , in which 90.0% of caregivers of children with CP did not executive an external professional activity.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, it is possible to infer that the mother is the main actor in child care, receiving help from her mother and her husband. Despite of this help, almost all participants did not any other labor outside the home, as in the study by Carvalho et al 17 , in which 90.0% of caregivers of children with CP did not executive an external professional activity.…”
Section: Discussionmentioning
confidence: 85%
“…Carvalho et al 17 , in a study with caregivers of children with CP, also reported that knowledge regarding aspects related to feeding difficulties was restricted, 66.6% of the sample were unaware of the definition of aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding practice education for CP Children have used several methods, and one of them is the lecture method. Giving lectures to caregivers on the topics of swallowing dynamics, swallowing disorders, care of children with dysphagia, and caregiver behavior in dealing with children's difficulties while eating (Carvalho et al, 2013). Education with film media has been carried out by Arora et al (2014).…”
Section: Introductionmentioning
confidence: 99%